Pull yourself up by your bootstraps: Identifying procedural preferences against helping others in the presence of moral hazard - Rostislav Staněk; Ondřej Krčál; Katarína Čellárová (Masaryk University, Faculty of Economics and Administration, 2021)
Governments and organizations often implement policies designed to help people in case of an undesirable event. Such policies can make the society better off, but they may also create moral hazard. We use a laboratory experiment to examine two questions. First, can discretionary decisions to provide assistance overcome the problem of moral hazard and lead to higher efficiency? Second, if so, will people prefer this discretionary procedure to the strict liability policy in which no assistance is provided? We find that the assistance is more ecient than the strict liability procedure. However, people still prefer the strict liability regime rather than assistance provision. We conduct additional treatments that show that this eect is not driven by the presence of the human discretion, nor by risk, loss or inequality aversion. This suggests that when moral hazard is a concern people have procedural preferences in favor of the strict liability regime.
Keywords: C91; D90; 330; Strict liability; Assistance; Procedural preferences; Experiment; Moral hazard